Moving towards a unified approach for the winding up of companies in view of the "repealed" chapter 14 of the Companies Act 61 of 1973 - Boraine, A. (Andre), 1957- (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2015.